TINJAUAN YURIDIS PENGATURAN TANAH DRUWE DESA DI BALI (ASPEK HUKUM PERLINDUNGAN MASYARAKAT ADAT ATAS TANAH) - I Gusti Agung Mas Rwa Jayantiari; I Ketut Kasta Arya Wijaya (Lembaga Penelitian, Universitas Warmadewa, 2017)
The regulation on community rights to land ownership is worth investigating considering that the development of law and policy issues of national land is apparently in line with the strategic value of land in the development. Thus, the reconstruction on state law and customary law in the regulation of community rights over the land is important so that the community rights are not neglected by the dominance of the right to control the land by the state. The management of village land in Bali (the land owned by the village called as druwe) is a concrete example that can be mentioned as the subject of land rights. Without having a clear law reference, it is then possible for the customary community to face difficulties in the control of their rights to the land owned by the customary village (desa pakraman). The community also does not have the legal protection that is strong enough to be used to defend their rights. This study is a normative juridical research that makes all of the problems are referred to judicial review as a system of norms that are used to give the prescriptive justification concerning the legal event. Results of the research showed that the land policy concerning the customary law community is governed by Article 3 of Act No. 5 of 1960 on the Basic Rules of Agrarian involving the recognition of indigenous peoples' rights although it is still limited. There is, even, a denial of the right to the land by other regional regulations related to land and natural resources. The rights of indigenous peoples, including druwe village land in Bali is set in accordance with to the concept of state law and customary law complementary without dominating one another. State law can be resolved all problems through the legal structure. Based on the theoretical aspects, settlement of land issues in the conception of state law and customary law can be thoroughly observed by putting the appropriate concepts and principles of the national land law that is still based customary law. Keywords: land ownership, customary village